2020
DOI: 10.1111/sji.12860
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the pathophysiology of gestational diabetes: Studies on local and peripheral immune cells

Abstract: Gestational diabetes mellitus (GDM) has been associated with impaired maternal immune response. Our aim was to review the available literature linking immune cells profile to GDM, in order to comprehend the role that different subpopulations play in the development of this pathology. We searched in PubMed for studies published in the last decade on circulating levels and placenta expression of immune cells on GDM. We identified 18 studies with several differences regarding the study design, clinical characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 54 publications
(159 reference statements)
1
24
0
Order By: Relevance
“…GDM is associated with an impaired maternal immune response. However, few studies have focused on the immune cell composition in GDM (37). We identified various types of immune cells in our specimens, including T/NK cells (1,628), B cells (247), monocytes (1,126) and macrophages (4,306).…”
Section: Immune Cell Subtypes In Human Placentamentioning
confidence: 98%
“…GDM is associated with an impaired maternal immune response. However, few studies have focused on the immune cell composition in GDM (37). We identified various types of immune cells in our specimens, including T/NK cells (1,628), B cells (247), monocytes (1,126) and macrophages (4,306).…”
Section: Immune Cell Subtypes In Human Placentamentioning
confidence: 98%
“…It is reported that GDM is associated with impaired maternal immune response. [ 26 ] Moreover, the differentially regulated proteins related to GDM identified by Zhao et al [ 27 ] also implicated in immune response and defense response. In addition, the enrichment analysis of the KEGG pathway showed that these MeDEGs were mainly enriched in “Allograft rejection,” “Graft-versus-host disease,” “Type I diabetes mellitus,” and “Autoimmune thyroid disease pathways.” This indicates that GDM is also involved in the pathway of type I diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that Th17 cells participate in the progression and development of diabetes mellitus, as well as GDM 5‐7 . Some publications have demonstrated that Th17 cells might promote GDM development 12,26‐28 . The percentage of Th17 cells and the ratio of Th17 cells to Tregs are significantly higher in GDM patients than non‐GDM pregnant women, and this trend is remarkably reduced after delivery.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Some publications have demonstrated that Th17 cells might promote GDM development. 12,[26][27][28] The percentage of Th17 cells and the ratio of Th17 cells to Tregs are significantly higher in GDM patients than non-GDM pregnant women, and this trend is remarkably reduced after delivery. Nevertheless, patients with GDM still have a higher Th17:Treg ratio than pregnant women without GDM even after delivery.…”
Section: Discussionmentioning
confidence: 99%